Developing Behavior-Based Assessment Scales To Promote Fairness In Performance Assessment - Rajuddin, Wa Ode Nursaadha; Eliza, Eliza; Nurdiana, Anne (Kompartemen: Kumpulan Orientasi Pasar Konsumen, 2024)
Performance appraisal is a critical process in human resource management that influences employee motivation, development, and recognition. However, challenges in performance appraisal are often associated with subjectivity and a lack of fairness in the assessment. Therefore, this research aims to develop a behavior-based assessment scale that can promote fairness in performance appraisal. The method of developing this assessment scale involves several key steps. First, identify relevant and objectively measurable assessment criteria, such as technical skills, teamwork, initiative, and integrity. Next, establish a clear and measurable assessment scale for each criterion, whether numerical scales or specific behavioral descriptions. Validation of the scale is conducted through testing and factor analysis to ensure its reliability and validity in accurately measuring behavior. Training for evaluators and relevant employees is also a crucial part of implementing this assessment scale to ensure consistent and objective evaluations based on established criteria. The results of developing this behavior-based assessment scale are expected to enhance transparency, objectivity, and fairness in the performance appraisal process. With a measurable and relevant assessment scale in place, it is hoped to motivate employees, identify areas for development, and provide fair recognition based on the actual contributions of each individual within the organization. This research makes a significant contribution in the context of human resource management towards achieving organizational goals effectively and efficiently.